THE INFLUENCE OF ALKALINE AND 2- BROMOETHANESULFONATE PRETREATMENT ON MICROBIAL FUEL CELL PERFORMANCE - Erna Saing, Putri
Indonesia is the largest palm oil producer in the world. In line with the increasing production of palm oil, wastewater such as palm oil mill effluent (POME) is also produced. POME has chemical oxygen demand (COD) levels that are substantially below the Indonesian government's quality standards. Therefore, it must be treated before being discharged into the environment. Microbial fuel cell (MFC) is a technology that can treat POME while generating electricity. MFC performance is measured by the value of power density, current density, and internal resistance that is strongly influenced by substrate conditions and microbial activity. Microbes in POME consist of exoelectrogens and methanogens, the presence of methanogens will inhibit the activity of exoelectrogen. This research was conducted to determine the effect of base (alkaline) and 2- bromoethanesulfonate (BES) pretreatment on the performance of MFC. The experiment was carried out by pretreatment with the addition of base at pH 7; 8; 9; and 10; which is combined with the addition of BES with a concentration of 50; 250; and 500 mol/L to optimize methanogen inhibition. Based on the experimental results, the highest values of open circuit voltage (OCV), current density, and power density that were obtained at variations in addition to pH 10 are 589 mV, 28.30 mA/m2, and 8.95 mW/m². Then the BES addition experiment was carried out at pH 10. The highest values of OCV, current density, and power density that were obtained at variations in addition to BES 250 mol/L are 649 mV, 3,611 mA/m2, and 1,301 mW/m². From the analysis of Electrochemical Impedance Spectroscopy (EIS), it was observed that the addition of base was dominated by charge transfer resistance and the addition of BES was dominated by ohmic resistance. COD removal efficiency ranged from 28-51% for base addition and 34-52% for BES addition. The increasing performance of MFC on variations of base addition and BES addition can be indicated that methanogen inhibition for exoelectrogen growth occurs optimally.